Perfect contrast visual cryptography scheme - HAN Yan-yan1; HE Wen-cai1; HU Yu-pu1 (Tongxin xuebao)
A perfect contrast visual cryptography scheme with the best contrast based on both the perfect black visual cryptography scheme（PBVCS） and the non-perfect black visual cryptography scheme（NPBVCS） was proposed.The proposed scheme applied simple Boolean operations to keep the consistency between the reconstructed image and the original secret image without pixel expansion and was easy to run.